Therapeutic Strategies for COVID-19 Lung Disease in Children - Gatti, Elisabetta; Piotto, Marta; Lelii, Mara; Pensabene, Mariacarola; Madini, Barbara; Cerrato, Lucia; Hassan, Vittoria; Aliberti, Stefano; Bosis, Samantha; Marchisio, Paola; Patria, Maria Francesca (Frontiers in Pediatrics, 2022)
The novel Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection has milder presentation in children than in adults, mostly requiring only supportive therapy. The immunopathogenic course of COVID-19 can be divided in two distinct but overlapping phases: the first triggered by the virus itself and the second one by the host immune response (cytokine storm). Respiratory failure or systemic involvement as Multisystem Inflammatory Syndrome in Children (MIS-C) requiring intensive care are described only in a small portion of infected children. Less severe lung injury in children could be explained by qualitative and quantitative differences in age-related immune response. Evidence on the best therapeutic approach for COVID-19 lung disease in children is lacking. Currently, the approach is mainly conservative and based on supportive therapy. However, in hospitalized children with critical illness and worsening lung function, antiviral therapy with remdesivir and immunomodulant treatment could be considered the “therapeutic pillars”.